Structural Design of Hybrid Fillers in a Polymer Matrix for Advanced Electromagnetic Interference Shielding - Uiseok Hwang; Jinwoo Lee; Seunghyun Kim; Xin Yang; Soochan Kim; Jonghwan Suhr; Jae‐Do Nam (Small Structures, 2025)
The rapid development of modern advanced electronic systems has created a pressing need for multifunctional polymer composites that can withstand external adversities such as electromagnetic waves, flames, and mechanical stresses. Although these requirements can be satisfied by incorporating different types of fillers, high filler loadings often lead to issues such as poor processability and increased material costs. Herein, a multifunctional polyamide‐6 composite is introduced using a carbon‐fiber flame‐retardant hybrid filler to design a next‐generation electromagnetic interference (EMI) shielding system. Based on the synergistic effect of the functionality and structural arrangement of these fillers in the composite, the EMI shielding system demonstrates high EMI shielding performance, improved mechanical properties, and excellent flame retardancy despite the low filler content. The scalability and multifunctionality of the proposed system highlight its potential for use in next‐generation applications, such as electric vehicles, aerospace, and 5G/6G telecommunications.